Rekonstruksi Fiqh Pendarahan Pervaginam dengan Pendekatan Medis - Musyafa’ah, Nur Lailatul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
This article discusses the reconstruction of fiqh (Islamic jurisprudence) with regard to vaginal bleeding using a medical approach. The fiqh of vaginal bleeding discusses menstruation, postpartum, and istiá¸¥Ã¢á¸ah. The discussion of fiqh is normative in nature, as it is based on the QurâÃ¢n and HadÃ®th. Technological developments in medical science affect the deconstruction of fiqh pertaining to vaginal bleeding. As a resut, the opinions of previous jurists become less relevant, and the fiqh of vaginal bleeding needs to be reconstructed accordingly. This reconstruction can be conducted by using the empirical-normative approach to the study of fiqh with regard tovaginal bleeding, redefining the fiqh of vaginal bleeding, reinterpreting the argument of fiqh concerning vaginal bleeding, and making medical experts as partners in determining vaginal bleeding.